Parents measuring pulses; an observational study. - White, J; Shepperd, S; Yudkin, P; Harnden, A; Mant, D (2004)
Parent reported pulse rates could provide important information on a child's clinical condition. The agreement between the parent's measurement of their child's pulse and a pulse oximeter was assessed following a brief educational intervention. Parents can be taught to measure the pulse of school age children, but have difficulty with preschool children.